Examining Batting Performance After a Sports-Related Concussion Among Major League Baseball Position Players. Issue 3 (March 2021) - Green, Gary; Pollack Porter, Keshia M.; Kvit, Anton; Conte, Stan; D'Angelo, John; Valadka, Alex; Curriero, Frank C.
Background: An ongoing challenge in sports-related concussion (SRC) is determining full recovery. This study examines performance metrics in baseball after an SRC and provides a template for assessment of return-to-performance parameters. Purpose: To determine whether batting performance returns to baseline after an SRC. Study Design: Descriptive epidemiological study. Methods: Participants were all Major League Baseball (MLB) position players with confirmed SRCs that occurred during the 2011-2015 seasons. A retrospective review and assessment of performance metrics before and after injury were conducted as defined relative to the number of plate appearances (PAs) to yield reliable performance statistics. Seven batting metrics were considered as outcomes in longitudinal regressions: batting average, on-base percentage, slugging percentage, on-base plus slugging, bases on balls, strikeouts, and home runs. Metrics were calculated for each player 60, 30, and 14 days before their SRCs, as well as for the 14, 30, and 60 days after returning to play. Other variables controlled for included defensive position, player age at the time of SRC, number of days missed, mechanism of injury, whether the player completed a rehabilitation stint, and year in which the mild traumatic brain injury (MTBI) occurred (2011-2015). Results: A total of 77 MTBI case events occurred in MLB position players over 5 seasons. These injuries resulted in a mean 11.4 days lost to injury. For all performance metrics using 60 or 30 days before MTBI as baseline, no statistically significant differences were found in batting performance. In total, 63 events met PA criteria before injury. Varying the PA cutoff thresholds to be more inclusive or more restrictive yielded similar regression results. For the 48 events that met PA criteria before and after injury, most performance metrics showed no significant performance change after MTBI and, in some events, a slight though mostly nonsignificant performance improvement after MTBI. Conclusions: MLB position players who are medically cleared to return to play after an SRC perform at the same offensive performance levels as their preinjury statistics when an adequate number of PAs is used to compare performance before and after injury.